2020
DOI: 10.1177/1591019920945059
|View full text |Cite
|
Sign up to set email alerts
|

Safety of stent-assisted coiling for the treatment of wide-necked ruptured aneurysm: A systematic literature review and meta-analysis of prevalence

Abstract: Background Stent-assisted coil embolization of ruptured wide-necked aneurysms is a controversial treatment modality due to concerns on the peri-procedural safety of anti-platelet therapy in the setting of acute subarachnoid hemorrhage. Our aim was to systematically review the literature on stent-assisted coil embolization of acutely ruptured wide-neck aneurysms to calculate the pooled prevalence of clinical outcome, thromboembolic and hemorrhagic complication rates and overall mortality. Methods We searched Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 59 publications
(70 reference statements)
3
9
1
Order By: Relevance
“…Several series have recently been published examining the efficacy of stentassisted coiling in the treatment of ruptured aneurysms. 22 In a recently published meta-analysis by Bsat et al, 22 the rates of postinterventional rebleeding (2.5%) and hemorrhagic complications (8.7%) were higher than the rates of these complications in the setting of WEB device deployment according to our metaanalysis. The risk of thromboembolic complications in the metaanalysis of Bsat et al was 9.1%, and this is also higher than that found in our study (6.8%).…”
Section: Discussioncontrasting
confidence: 42%
“…Several series have recently been published examining the efficacy of stentassisted coiling in the treatment of ruptured aneurysms. 22 In a recently published meta-analysis by Bsat et al, 22 the rates of postinterventional rebleeding (2.5%) and hemorrhagic complications (8.7%) were higher than the rates of these complications in the setting of WEB device deployment according to our metaanalysis. The risk of thromboembolic complications in the metaanalysis of Bsat et al was 9.1%, and this is also higher than that found in our study (6.8%).…”
Section: Discussioncontrasting
confidence: 42%
“…The SAC technique in EVT of ruptured aneurysms has higher overall perioperative complications than the non-SAC techniques. 14,15 In our study, similar to the literature, we found that SAC for the treatment of ruptured WNAs had the highest complication rates compared to cBAC and mBAC (p < 0.05). The complication rates of SAC, including thromboembolic events, increase up to 10-fold during the acute phase of SAH.…”
Section: Discussionsupporting
confidence: 87%
“…27 The proportion of patients who underwent SAC for ruptured WNAs and had favorable clinical outcomes were reported as 66-88% in a literature review. 15 In our study, we observed that the angiographic and clinical outcomes in the SAC group were comparable to those in the literature. The favorable angiographic outcomes of the SAC and mBAC techniques were similar at the 6 th -month follow-up (p > 0.05).…”
Section: Discussionsupporting
confidence: 86%
“…Our finding is similar to previous studies that showed the incidence of thromboembolic complications was 7.8–15% after SAC of ruptured intracranial aneurysms ( 14 17 ). Bsat et al ( 18 ) systematically reviewed the literature on SAC of acutely ruptured aneurysms in 1,582 patients and found that the overall rate of thromboembolic complications was 9.1% (95% CI: 6.0–12.7%; I = 72.8%). There was a high rate of thromboembolic complications, probably because of insufficient coverage of antiplatelet therapy or antiplatelet resistance ( 19 ).…”
Section: Discussionmentioning
confidence: 99%